Study of Velopharyngeal Movement in Cleft Palate Patients Following Pharyngeal Flap Surgery - SONODA, Takaaki (Journal of Japanese Cleft Palate Association, 2001)
This study investigated the change in velopharyngeal movement following pharyngeal flap surgery. The subjects were six patients who underwent pharyngeal flap surgery because of velopharyngeal incompetence (the pharyngeal flap group). Seven normal adults (the normal group), and seven surgically treated cleft palate patients with normal speech (the recovered cleft group), were selected as control groups. EMG of m. levator veli palatini, and the strength of velopharyngeal closure and intraoral air pressure during phonation, blowing, and swallowing, were measured preoperatively, and at 3 months,6 months, and 1 year postoperatively. Nasal air flow rates were analyzed in the pharyngeal flap group as well. Speech intelligibility testing was carried out on the pharyngeal flap group and the recovered cleft palate group. Results were as follows: 1. prepearatively, EMG activities, strength of velopharyngeal closure and intraoral air pressure during blowing and pressure consonants were significantly lower than in the normal group and the recovered cleft palate group. Following pharyngeal flap surgery, those values increased significantly, becoming close to the level in the recovered cleft palate group. 2. The preoperative value of EMG activities and strength of velopharyngeal closure were the lowest during phonation of nasal consonant sounds. These parameters were as low as those of the two control groups, and no remarkable changes were observed until 1 year postoperatively. Preoperative values of EMG activity and strength of velopharyngel closure during swallowing were as high as those of the recovered cleft palate group, and there were no remarkable postoperative changes. 3. There was no correlation between EMG activity and intraoral air pressure preoperatively, but these parameters were correlated postoperatively. 4. Speech intelligibility improved remarkably following pharyngeal flap surgery. Still, at one-year postoperatively, it remained lower than that in the recovered cleft palate group.